Two new species of cave-dwelling Charinus Simon, 1892 from Brazil (Arachnida: Amblypygi: Charinidae) - Vasconcelos, Ana Caroline Oliveira; Ferreira, Rodrigo Lopes (Zootaxa, 2017)
Two new species of the genus Charinus are described from caves of Brazil: Charinus spelaeus sp. n., the fourth described species of the genus for the state of Minas Gerais, and Charinus santanensis sp. n., the sixth described species of the genus for the state of Bahia. Charinus spelaeus sp. n. has reduced median and lateral eyes, and is the sixth troglobitic Charinus described for Brazil. We present here an updated key and a distribution map for all the Brazilian species of Charinus.